Pastures in tropical farming systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Tropical pasture utilization by L R Humphreys 205pp 1991 ISBN 052138030 8 published by Cambridge University Press Trumpington Street Cambridge CB2 1RP UK